Urgensi Studi Ekonomi Islam - Ahmad Dahlan (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Islamic economy discourse tend to viewed as no more than conventional economy that developed with ethic-religious content, but actually itâ€™s have wide and specific area. To elaborate that width, nowadays urgently needed a study media or special education related with Islamic economy science discipline. The aim is to produce economist that have humanist and religious mental, therefore economy can maintain its religious norms.Â